Studies on Mechanism of Activity of Fly Ash-Cement Slurry Improved by High-Energy Ball Milling - Cheng, Xiaowei; Gu, Tao; Huang, Sheng; Li, Zaoyuan; Guo, Xiaoyang (Asian Journal of Chemistry, 2012)
In this paper, high-energy ball milling is used to slove the problem of low utilization factor of fly ash caused by its low activity in fly ash-cement slurry. The particle size distribution of fly ash-cement slurry and the hydration products, microstructure and pore structure of fly ash-cement paste were studied by using the laser particle size analyzer, scanning electron microscope, X-ray diffraction. The mechanism of high-energy ball milling increasing activiy of fly ash in fly ash-cement slurry is discussed in terms of theory. The experimental results demonstrate that properties of fly ash-cement slurry is perfect and the early strength of fly ash-cement paste is excellent and its microstructure is compact. These improvements are bacause of the the pozzolanic reaction between portlandite (CH) and active materials of fly ash. The reasonable composition of hydration products and compact microstructure provid excellent durability to fly ash-cement paste.